Penguatan Kesadaran Perbaikan Lingkungan melalui Participatory Action Research Dusun Gedok Wisata B29 - Farida, Laili Nur; Chomsa, Diah Agustina; Hidayati, Nurul; Munir, Sirojum; Asegaf, Muhammad Maulana; Junjunan, Mochammad Ilyas (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
One of the interesting tourist destinations in Lumajang Regency is B29 Tourism Village in Argosari Village, Senduro District. From here, visitors can enjoy views of Mount Bromo, the highest peak in the Sand Sea area, which is located about 40 kilometers from Lumajang City and has a height of about 2900 meters above sea level. Argosari Village also has amazing natural beauty, making it an attraction for tourists. The Lumajang Regency Government has a policy that regulates the tourism sector through the cultural tourism office. Garbage is a common problem for the wider community, especially in the people of Gedok Hamlet, Argosari Village, Senduro District, Lumajang Regency. The unavailability of trash bins has led to the habit of burning garbage which can cause air pollution, and throwing garbage in vacant land or ravines which can cause environmental damage. This service focuses on the waste problems that occur in Gedok Hamlet, to reduce littering we provide several trash cans that can be useful for Gedok Hamlet residents to dispose of waste in its place. This service uses the PAR (Participatory Action Research) method, which involves community participation through interviews and observations of the community around Gedok Hamlet as a data source. This service aims to provide benefits and good impacts on waste problems that occur both in Gedok Hamlet and in the wider community, so that they understand the impact of waste on the environment and health.